Enhancing Vocabulary Acquisition Through Word Association Recitation at EFL Students - Rikarno Putra, Andika; Mulyadi, Dodi; Aimah, Siti; Ginting, Pirman; Singh, Charanjit Kaur Swaran (Universitas Muhammadiyah Sidoarjo, 2025)
Vocabulary is one of the key components to mastering English. The school is a place where EFL students could start learning English. This study aimed to find out whether or not the word association recitation could enhance vocabulary acquisition among beginner-level EFL students at an Islamic junior high school. This quantitative study employed a Classroom Action Research (CAR) design to investigate the effectiveness of the word association recitation technique in improving vocabulary acquisition among seventh-grade students at an Islamic junior high school. Conducted over two cycles between October and November 2024, each cycle consisted of three instructional sessions. A purposive sampling method was used to select Class 7A (N = 143), which consisted of students with varied levels of prior English exposure. The results indicated significant improvement in classroom engagement, with attention increasing from 46% to 67%, participation from 47% to 71%, and positive attitudes from 57% to 74%. Notably, post-test scores rose by 46.7%, from an average of 49.23 to 72.23, with substantial gains among lower-proficiency learners (up to 122% improvement). A paired samples t-test revealed a statistically significant difference between pre- and post-intervention scores (p = .000), confirming the positive impact of the technique on vocabulary learning. Future research is encouraged to explore the integration of communicative tasks, test the approach across broader EFL contexts, and incorporate digital tools to enhance vocabulary practice.